Katuk (Sauropus androgynus (L.) Merr.) dan Produksi Air Susu Ibu - Eni Folendra Rosa; Aisyah Aisyah; Nelly Rustiati; Zanzibar Zanzibar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of giving katuk (Sauropus androgynus (L.) Merr.) to increase breast milk production. The method used is a quasi-experimental pretest-posttest non-equivalent control design for breastfeeding mothers in Lubuk Batang District, determined by quota sampling technique for as many as 60 people. Data analysis was performed by independent t-test to see the difference in breast milk production changes in the intervention and control groups. The results showed that the increase in breast milk production in the intervention group was 262.96 ml, while in the control group, it was 126.46 ml. The vegetable katuk intervention increased breast milk production by 107.9% more than the control group with an -value of 0.000. In conclusion, giving katuk vegetables to breastfeeding mothers is proven to increase breast milk production. Keywords: Breast Milk Production, Sauropus androgynus (L.) Merr.